Clinicopathological Study of 307 Patients with Lichen Planus Actinicus and Pigmentosus Referred to Razi Skin Hospital from 2016 to 2021 - Kambiz Kamyab; Zahra Gholi; Maryam Ghiasi; Marzieh Pirzadeh; Maryam Nasimi (Mattioli1885, 2023)
Introduction: The two less-known subtypes of lichen planus (LP) are lichen planus actinicus (LPA) and lichen planus pigmentosus (LPP), with the highest prevalence in the Middle East. Objectives: We aimed to evaluate the clinicopathological profile of these patients. Methods: 307 cases including 184 LPA and 123 LPP patients were recruited from the registered pathology reports of Razi Skin Hospital of Tehran from April 2016 to March 2021. The clinical features and pathological reports were extracted and analyzed. Results: Among 307 patients, 117 (63.9%) in the LPA group and 88 (71.5%) in the LPP group were women. Duration of disease ranged from 1 month to 20 years and 1 month to 12 years in the LPA and LPP groups, respectively. Face (159 patients), limbs (68), and neck (23) were the most frequent sites of involvement in LPA patients, whereas face (60 patients), limbs (47), and trunk (42) were more commonly involved in the LPP patients. Pruritus and oral mucosal lesions were found with similar frequency in both groups. Pathological evaluation showed vacuolar degeneration of basal layer (100%), lymphocytes infiltration (97.3%), and melanin incontinence (58.2%) as the most frequent findings in LPA and vacuolar degeneration of basal layer (100%), lymphocytes infiltration (100%), and melanin incontinence (52/8%) as the most frequent findings in LPP cases.Conclusion: LPA and LPP were both more prevalent among women.  Face was the most common site of involvement in both LPA and LPP. Vacuolar degeneration, lymphocyte infiltration, melanin incontinence, and hyperkeratosis were more common histological findings in this study.